Anti-Inflammatory Activity of Ayurvedic Trikatu Herbal Oil and Identification of Its Phytochemical Constituents Using GC-MS - Putu Era Sandhi Kusuma Yuda; Ni Luh Kade Arman Anita Dewi; Maria Malida Vernandes Sasadara; Dewa Ayu Ika Pramitha; Erna Cahyaningsih (JST (Jurnal Sains dan Teknologi), 2025)
Osteoarthritis (OA) is a degenerative joint disease characterized by chronic inflammation, which can lead to progressive joint dysfunction and disability. Long-term use of conventional pharmacological therapies is often associated with serious side effects, highlighting the need for safer and more effective alternative treatments. This study aims to analyze the effectiveness and underlying anti-inflammatory mechanisms of topical Trikatu Herbal Oil (THO) by assessing physiological responses and identifying active compounds through phytochemical analysis and Gas Chromatography–Mass Spectrometry (GC–MS). This research employed an experimental approach using a post-test only control group design. The study subjects consisted of 24 male BALB/c mice aged 2–3 months, weighing 20–30 g. Anti-inflammatory activity was evaluated using a carrageenan-induced paw edema model, in which edema volume was measured hourly for four hours using a plethysmometer. Data were obtained from observations of edema volume changes and GC–MS analysis of the bioactive constituents of THO. Statistical analysis was performed using the Kruskal–Wallis and Mann–Whitney tests at a 95% confidence level. The results demonstrated that Trikatu herbal oil contains β-caryophyllene and fatty acids that play a role in suppressing inflammatory responses. THO at a 20% concentration exhibited the highest anti-inflammatory activity, with an edema inhibition percentage of 56% compared to the control group. These findings confirm that Trikatu herbal oil is significantly effective as a topical anti-inflammatory agent. Implicatively, this study provides a scientific basis for the development of safe, natural-based topical herbal therapies with strong potential as alternatives to long-term synthetic anti-inflammatory treatments.